Hemostasis and Alterations of the Central Nervous System - del Zoppo, Gregory J.; Izawa, Yoshikane; Hawkins, Brian T. (Seminars in Thrombosis and Hemostasis, 2013)
Modulation of coagulation has been successfully applied to ischemic disorders of the central nervous system (CNS). Some components of the coagulation system have been identified in the CNS, yet with limited exception their functions have not been clearly defined. Little is known about how events within the cerebral tissues affect hemostasis. Nonetheless, the interaction between cerebral cells and vascular hemostasis and the possibility that endogenous coagulation factors can participate in functions within the neurovascular unit provide intriguing possibilities for deeper insight into CNS functions and the potential for treatment of CNS injuries. Here, we consider the expression of coagulation factors in the CNS, the coagulopathy associated with focal cerebral ischemia (and its relationship to hemorrhagic transformation), the use of recombinant tissue plasminogen activator (rt-PA) in ischemic stroke and its study in animal models, the impact of rt-PA on neuron and CNS structure and function, and matrix protease generation and matrix degradation and hemostasis. Interwoven among these topics is evidence for interactions of coagulation factors with and within the CNS. How activation of hemostasis occurs in the cerebral tissues and how the brain responds are difficult questions that offer many research possibilities.
Keywords: coagulation factors; hemostasis; central nervous system; knockouts; neurovascular unit